(untitled) (The Agriculturists, 2012)
An experiment was conducted at the research field of Tuber Crop Research Centre (TCRC) of Bangladesh Agricultural Research Institute, Gazipur during the winter of 2006-2007 to determine the effects of cutting methods and seed size on the yield and profitability in potato (Solanum tuberosum L.). It was observed that the foliage coverage, plant height, stems/hill, number and weight of tubers/plant varied significantly due to variation of tuber size. The highest germination index (18.13) was found when large size whole tuber was used followed by small size whole tuber and medium size whole tuber. Vigorous plants, maximum plant height and the number of stems/ hill at 60 DAP were also produced when the crop was raised from large size whole tubers. The maximum leaf area of 3909 cm2 was found in medium size –half proximal treatment. The highest number (10.23) and weight of tubers/ hill (0.40 kg) were observed in T6 large size-whole tuber treatment. The highest gross yield of tubers (25.10 t/ha) was also produced when large whole tubers were used. However, small tuber size and half cut distal would be economically profitable for enhancing growth and yield of potato. Keywords: Potato; seed size; cutting methods; profitability DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9479 The Agriculturists 2011; 9(1&2): 54-62